Machine learning application in reservoir water level forecasting for sustainable hydropower generation strategy - Sapitang M.; Ridwan W.M.; Kushiar K.F.; Ahmed A.N.; El-Shafie A. (MDPI, 2023)
alternative energy; data set; hydroelectric power plant; machine learning; power generation; precipitation intensity; scenario analysis; sustainable development; uncertainty analysis; water level; Malaysia